Pengaruh Keterlibatan Karyawan, Budaya Organisasi, dan Gaya Kepemimpinan terhadap Komitmen Organisasional dalam Meningkatkan Kinerja Karyawan (Studi pada Universitas Brawijaya) - Indayati, Nurul (Jurnal Aplikasi Manajemen, 2012)
This study aims to analyze the influence of employee involvement, organizational culture andleadership style on organizational commitment in improving performance. Inferential statistical analysisused was SEM (Structural Equation Modeling) by collecting data through a survey of administrative staffat UB as much as 130 repsonden. The analysis proved that there is a positive influence signifikant betweenemployee engagement, organizational culture and leadership style on organizational commitment, a positiveinfluence signifikant between employee engagement, organizational culture, leadership style andorganizational commitment to employee performance.